2020
DOI: 10.1177/0363546519898716
|View full text |Cite
|
Sign up to set email alerts
|

An Intact Ligamentum Teres Predicts a Superior Prognosis in Patients With Borderline Dysplasia: A Matched-Pair Controlled Study With Minimum 5-Year Outcomes After Hip Arthroscopic Surgery

Abstract: Background: Hip arthroscopic surgery in patients with borderline dysplasia continues to be controversial. In addition, it has been suggested that ligamentum teres (LT) tears may lead to inferior short-term patient-reported outcomes (PROs) when compared with a match-controlled group. Purposes: (1) To report minimum 5-year PROs in patients with borderline dysplasia and LT tears who underwent hip arthroscopic surgery and (2) to compare these PROs to those of a matched-pair control group of patients with borderlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…Furthermore, the definition of borderline dysplasia varies across the literature, and the cutoff values used in the present study, albeit previously reported, may be perceived as arbitrary. 6,31 Arthroscopic management of patients with acetabular borderline dysplasia has evolved toward capsular plication and labral reconstruction/augmentation (when labral repair is not amenable), instead of capsulotomy without repair and selective labral debridement. 13,28 Therefore, while the borderline dysplasia and control groups contain patients who underwent labral selective debridement, patients with the same surgical findings in the current day would be treated with a labral restoration alternative.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the definition of borderline dysplasia varies across the literature, and the cutoff values used in the present study, albeit previously reported, may be perceived as arbitrary. 6,31 Arthroscopic management of patients with acetabular borderline dysplasia has evolved toward capsular plication and labral reconstruction/augmentation (when labral repair is not amenable), instead of capsulotomy without repair and selective labral debridement. 13,28 Therefore, while the borderline dysplasia and control groups contain patients who underwent labral selective debridement, patients with the same surgical findings in the current day would be treated with a labral restoration alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were excluded if they had a Tönnis grade >1 or previous hip conditions (Legg-Calve-Perthes disease, avascular necrosis, or slipped capital femoral epiphysis). Two groups were created: the study group with borderline dysplasia defined as a lateral center-edge angle (LCEA) between 18° and 25° (Figure 1) 31 and a control group with normal coverage (LCEA, 26°-40°). This study was approved by an institutional review board.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature has suggested that LT tears may portend an inferior outcome. This past March, Maldonado et al 12 reported on 5-year outcomes of a matched-pair study comparing patients with and without LT tears in association with borderline dysplasia. Although the patient reported outcomes were generally favorable for both groups, the group undergoing LT debridement for tears had inferior patient acceptable symptomatic states for the modified Harris Hip Score (75% vs 100% of the control group).…”
Section: See Related Article On Page 2170mentioning
confidence: 99%
“…Although the patient reported outcomes were generally favorable for both groups, the group undergoing LT debridement for tears had inferior patient acceptable symptomatic states for the modified Harris Hip Score (75% vs 100% of the control group). 12 Limited reports of LT reconstruction have offered a new treatment option that has had generally favorable outcomes. 13,14 Hip arthroscopy in patients with EDS has also been reported.…”
Section: See Related Article On Page 2170mentioning
confidence: 99%